Radius Problems for Starlike Functions Associated with the Tan Hyperbolic Function. (20th September 2021) - Ullah, Khalil; Zainab, Saira; Arif, Muhammad; Darus, Maslina; Shutaywi, Meshal
Abstract : The aim of this particular article is at studying a holomorphic function f defined on the open-unit disc D = z ∈ ℂ : z < 1 for which the below subordination relation holds z f ′ z / f z ≺ q 0 z = 1 + tan h z . The class of such functions is denoted by S tan h ∗ . The radius constants of such functions are estimated to conform to the classes of starlike and convex functions of order β and Janowski starlike functions, as well as the classes of starlike functions associated with some familiar functions.